(untitled) (Al-Qamar, 2025)
This article explores the role of Sufism in the restoration of mental health through an analytical study of the ethical and spiritual teachings found in Kashf al-Mahjub, the renowned work of Hazrat Ali Hujwiri (Data Ganj Bakhsh). The study highlights how Sufi principles—such as knowledge of God (tawhid, faith, and purity), repentance and its related practices, love, generosity, and social etiquette—not only serve as a pathway to spiritual refinement but also align closely with contemporary psychological approaches, including Cognitive Behavioral Therapy, Mindfulness, and Positive Psychology. By examining these parallels, the paper aims to establish a meaningful dialogue between classical Sufi wisdom and modern psychological frameworks, demonstrating how Sufi teachings can contribute significantly to mental well-being in today’s world.